Influence of Performance Appraisal on Performance of Universities in Machakos and Kitui Counties, Kenya - Mbiti, Annah Mumbua; Arasa, Robert; Kinyili, Jacinta (European Journal of Business and Management Research, 2019)
Through performance appraisal an organization undertakes to measure the set goals against employee actual performance with respect to the period in question. It is also used to identify an employee’s weaknesses and strengths and provide for appropriate adjustments. This study examined the influence of performance appraisal on organizational performance in Universities within Machakos and Kitui Counties in Kenya. A descriptive research design was adopted and both qualitative and quantitative data was collected. The study targeted staff working in the selected departments of administration, human resource, finance and audit, procurement, deans of schools and directorate of quality assurance. Stratified sampling procedure was used from which 45 out 263 respondents were targeted. Purposive sampling was then employed because the study was interested in heads of departments. The main data collection tool was the questionnaire with both open and closed ended questions. In addition interviews were conducted with some heads of departments to ascertain some of the information in the questionnaires. Both descriptive and inferential statistics analysis was used to aid addressing the objective of the study. The study findings revealed that there was effective performance appraisal procedures and methods in place that were used by the management within the universities studied in assessing the employees performance on the set targets of the universities. The correlation coefficients and regression analysis result indicates that performance appraisal has a positive and statistically significant influence on human resource on performance of universities; P<0.05(P=0.00) with explanatory power of 78.7%. The study recommends that clear job descriptions for each staff should be well spelt out as this in the basis for appraising the employees. This will mitigate against possible situations of confusion and dissatisfaction of employees which arises when they do not understand what is expected of them leading to failure in meeting their set targets. University managements should also ensure that there is participatory target setting, aligning the same to the bigger goals of the university and adequate staff support in the execution of set targets as this has implications on the overall performance of the institution.
Keywords: Organizational Performance; Performance Appraisal; Performance Appraisal Methods; Universities